Effects Of Annealing Growth Conditions Of β-Β-Ga2O3 Thin Films For Solar Blind Uv Photodetectors By Using Sol-Gel Dip Coating Method - Hamid, Maizatul Akmam Ab; Sha, Shiong Ng; Hassan, Zainuriah (2020)
In this paper, the effects of different annealing growth conditions on the structural, surface morphology and optical properties of the grown β-Ga2O3 thin films on pSi(100) substrates via sol-gel dip coating were reported. Field-emission scanning electron microscopy observations shows uniform and densely packed grains as well as decreasing pinholes are formed at annealing temperatures of 900⁰C. As the annealing temperatures increase from 700⁰C to 1200⁰C, the crystallinity of the β-Ga2O3 (400) peak at 900⁰C shows improved quality as well as increases crystallite size, D and decreasing FWHM value. The root-mean-square (rms) surface roughness of the deposited β-Ga2O3 thin films increases from 0.479 nm to 91.0 nm when annealing temperature increased from 700⁰C to 1200⁰C and exhibits nanocrystalline structure at 900⁰C. FTIR measurements demonstrated that the reflectivity spectra of β-Ga2O3 thin films increases from 700⁰C and diminishes above 1000⁰C. Finally, all the results revealed that 900⁰C in air ambient was the best annealing growth conditions to deposit β-Ga2O3 thin film and have high potential for deep UV photodetector applications.